(untitled) (Global Journals of Research in Engineering, 2024)
Durability of concrete structures is of great concern among civil engineering community The concrete is one of the most widely used construction materials due to its relatively competitive affordability versatility easy availability of its raw materials workability and mouldability to any shape and size 1 Concrete is a composite material that consist of binding medium and aggregates particles Once the concrete in set it has three phases namely cement paste the aggregate and the interfacial transition zone ITZ between them 2 3 The durability of cementitious materials is seriously affected by the service environments of the concrete The service environment comprises several aggressive ions and are transported into the concrete through the pores capillary pores voids cracks microchannels nanochannels and these ions react with the cementitious materials and as a result deterioration of concrete as well as embedded reinforcing steel is caused Among these concrete defects the capillary porosity and pores connectivity from the surface of concrete to the interior of concrete is of great concern from durability point of view 4 Surface coatings or overlays on concrete can prevent entry of aggressive ions from environment to the concrete However the durability of coating or overlays are questionable